A-Star and SMART Methods for Islamic Boarding School Recommendations in North Aceh and Lhokseumawe - Fuzna Febriani; Dahlan Abdullah; Rini Meiyanti (Politeknik Negeri Lhokseumawe, 2026)
Advances in information technology have increased the public’s need for systems capable of providing information quickly and easily, including in searching for Islamic boarding schools. This study developed a web-based Geographic Information System (GIS) to recommend Islamic boarding schools in North Aceh and Lhokseumawe using the Simple Multi-Attribute Rating Technique (SMART) method and the A-Star algorithm. The SMART method determines rankings based on four criteria: location, accreditation, number of students, and type of boarding school through weighting, min-max normalization, and utility calculation. A-Star is applied to find the shortest route using the Haversine formula. The dataset consists of 361 verified boarding schools from the Dayah Education Office. Black box testing confirms all system functions are valid. Results show Dayah Darul Yaqin achieved the highest SMART score of 81.44 with a distance of 0.3 km, followed by Imam Syafi’i with 80.66 and 0.88 km, demonstrating that the SMART-A-Star integration produces objective and efficient recommendations.